Kesenjangan Sosial Antar Peserta Didik Di SMA Negeri 1 Luwuk - Anwar, kasmayani-@; Lisabe, Chandra M; Ledo, Sagita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tompotika Luwuk, 2025)
This research aims to describe the problem of social inequality between students with different backgrounds and social status. This research was carried out at SMA Negeri 1 Luwuk for the 2023/2024 academic year. The method used in this research is descriptive qualitative with research subjects consisting of 6 informants, namely 3 teaching staff and 3 students. The method used in this research is descriptive qualitative. The data collection technique consists of 3 stages, namely the observation, interview and documentation stages. The data analysis techniques used in this research are data collection, data reduction, data presentation, and drawing conclusions. The results of the research reveal that the problem of social inequality between students is influenced by factors from various social backgrounds of students. Efforts to overcome this social gap can be carried out with academic and non-academic learning programs in schools by teaching staff. Keywords: Social Inequality, Student